Assessing the impact of understory vegetation cut on soil epigeic macrofauna from a cork-oak Montado in South Portugal - Mendes, Sara Margarida; Santos, Joaquim; Freitas, Helena; Sousa, José Paulo (Agroforestry Systems, 2011)
Cork oak ‘‘Montados’’ are a particular Mediterranean ecosystem, which can be found in Southern Portugal. Portuguese ‘‘Montados’’ are manmade ecosystems, mainly used for cork production and cattle farming, that support a high biological diversity. Current sustainable management techniques imply a shrub clearing with heavy machinery, which can be highly disruptive for soil biota. In order to evaluate the effects of understory vegetation management on soil epigeic macrofauna, ﬁve zones were deﬁned along a chronosequence of shrub clearing: a non-disturbed zone (zone 5) and zones where understory vegetation was cut at 4–5 years (zone 4), at 3–4 years (zone 3), at 2 years (zone 2) and at 1 year (zone 1). A sixth zone (zone 6) was selected in a pasture, where cattle are occasionally present. Soil fauna was sampled using ‘‘pitfall’’ traps and sampling took place in autumn 2003. A total of 2,677 individuals, separated into 152 species and morphospecies, were caught in the traps. With the exception of zone 6, that presented a lower number of species, all the other zones from the chronosequence presented, in most cases, a similar number of taxa, species diversity (Shannon) and species richness (Margalef). Multivariate analysis separated recently disturbed zones (plus zone 6) from those intervened at longer time; groups like Formicidae, Scydmaenidae, most families from Araneae and insect larvae appeared closely associated to zones 3–5 (with a higher shrub cover and thick litter layers), whereas, other Hymenoptera, Gastropda and most Coleoptera families, appeared associated to recently disturbed zones (zones 1 and 2) and to zone 6, characterized by a lower shrub cover and a lower accumulation of litter. This separation indicates that effects of the intervention can endure for 2 or 3 years. After that time, the normal natural regeneration of the understory vegetation seems to support the restoration of the macrofauna community, thus indicating that the sustainable management strategy adopted, i.e., making a shrub cut every 5–6 years, seems not induce a signiﬁcant effect on local species richness of soil epigeic macrofauna.
Keywords: Biodiversity; cork-oak forests; soil macrofauna; sustainable management; understory management

Fungal fruitbodies and soil macrofauna as indicators of land use practices on soil biodiversity in Montado - Azul, Anabela Marisa; Mendes, Sara Margarida; Sousa, José Paulo; Freitas, Helena (Agroforestry Systems, 2011)
The impacts of land use on soil biodiversity are still poorly understood, although soil fungi and macrofauna are recognized to provide beneÞts to ecosystems. Here, we tested whether land use practices used to control shrub density inßuences the fruiting macromycetes (ectomycorrhizal-forming fungiÑ ECMFÑand saprobes) and soil macrofauna diversity and abundance in Montado ecosystems. To address this inßuence, we conducted a 2-yearsÕ period monitoring of fungi fruitbodies and macrofauna in sixteen experimental plots in Montado landscape in southern Portugal. A total of 4,881 frutibodies (57 taxa of ECMF and 64 taxa of saprobic fungi) and 3,667 soil invertebrates (73 species and morphospecies) were monitored in the experimental plots. There was greater losses in sporocarps production and taxa composition, particularly the ECMF, in plots where shrub density was controlled by permanent grazing (Ca) or involving cutting practices followed by soil tillage (M), in comparison with cutting practices with no soil tillage (Cu) and the control (C). The ECMFLaccaria laccata and Xerocomus subtomentosus exhibited a close relation with C and Cu plots while the saprobes, e.g., Entoloma conferendum, were associated to Ca and M plots. Most species associated to Cu plots were present in C plots during the 2 years, but not in Cu after the cutting practices (in the second year of sampling). Regarding soil macrofauna, higher values of taxa and species richness were observed in C and Cu plots in the Þrst year of sampling. The ant species Aphaenogaster senilis and several Staphylinid morphospecies exhibited a close relation with M plots, whilst most spider families were directly associated to C and Cu plots. After the shrub cutting practices, higher values of taxa and species richness of soil macrofauna were observed in M and Ca plots; the presence of species with a high competitive ability to colonize disturbed areas faster might explain the results. Contrary to the frutibodies production and diversity, species richness and abundance within soil macrofauna were identical between Cu and C in 2004. Thus, fruiting macromycetes and soil macrofauna diversity and abundance in MontadoÕs, appear highly sensitive to land use and somewhat reßected a trend of severity to the current shrub management practices.
Keywords: Ecosystems monitoring; Fungal fruit-body; fungal fruit-body á soil; land use; macrofauna á; montado; Quercus suber L.; soil macrofauna

Annual feeding rate of the millipede Glomeris marginata on holm oak ( Quercus ilex) leaf litter under Mediterranean conditions - DAVID, J. F.; Gillon, Dominique (Pedobiologia, 2002)
The annual consumption and assimilation rates of Quercus ilex leaf litter by the millipede Glomeris marginata were estimated under Mediterranean conditions simulated in the laboratory. Measurements were made on six occasions throughout the year to take into account seasonal variations in (i) the quality of decomposing leaves, (ii) the physiological state of the animals, and (iii) temperature plus photoperiod. The mean weight-specific consumption rate was 14 g (dry weight) g-1 (live weight) y-1 , which is much higher than published figures for Mediterranean oak leaf litter. The consumption rate was highest in spring (51 mg g-1 d-1 ) and lowest in summer (28 mg g-1 d-1 ), the summer consumption rate being even lower when determined with air-dried leaves (17 mg g-1 d-1 ). Assimilation efficiency averaged 6 % for the year, with a maximum in spring (9 %) and a minimum in winter (1 %). A much higher assimilation efficiency (29 %) was measured with freshly fallen leaves, but a food preference experiment showed that these leaves were generally avoided and that G. marginata preferred more decomposed leaves despite their lower digestibility. It is concluded that these saprophagous macroarthropods – with field biomasses of 7–11 g (live weight) m-2 – produce considerable amounts of faecal pellets in Mediterranean oak forests.
Keywords: assimilation efficiency; diplopoda; feeding rate; Mediterranean forests; soil macrofauna

Annual feeding rate of the millipede Glomeris marginata on holm oak ( Quercus ilex) leaf litter under Mediterranean conditions - David, J F; Gillon, Dominique (Pedobiologia, 2002)
The annual consumption and assimilation rates of Quercus ilex leaf litter by the millipede Glomeris marginata were estimated under Mediterranean conditions simulated in the laboratory. Measurements were made on six occasions throughout the year to take into account seasonal variations in (i) the quality of decomposing leaves, (ii) the physiological state of the animals, and (iii) temperature plus photoperiod. The mean weight-specific consumption rate was 14 g (dry weight) g-1 (live weight) y-1 , which is much higher than published figures for Mediterranean oak leaf litter. The consumption rate was highest in spring (51 mg g-1 d-1 ) and lowest in summer (28 mg g-1 d-1 ), the summer consumption rate being even lower when determined with air-dried leaves (17 mg g-1 d-1 ). Assimilation efficiency averaged 6 % for the year, with a maximum in spring (9 %) and a minimum in winter (1 %). A much higher assimilation efficiency (29 %) was measured with freshly fallen leaves, but a food preference experiment showed that these leaves were generally avoided and that G. marginata preferred more decomposed leaves despite their lower digestibility. It is concluded that these saprophagous macroarthropods – with field biomasses of 7–11 g (live weight) m-2 – produce considerable amounts of faecal pellets in Mediterranean oak forests.
Keywords: assimilation efficiency; diplopoda; feeding rate; Mediterranean forests; soil macrofauna

The use of near infrared reflectance spectroscopy to study chemical changes in the leaf litter consumed by saprophagous invertebrates - Gillon, D; David, J F (SOIL BIOLOGY & BIOCHEMISTRY, 2001)
Chemical changes in holm oak leaf litter that was consumed by the millipede Glomeris marginata were studied using near infrared reflectance spectroscopy. Compared to leaf litter, faecal pellets were significantly richer in lignin and poorer in nitrogen and readily assimilable constituents. The C:N ratio was significantly higher in the faeces. A NIRS-predicted index of litter decomposability was found to be lower in the faeces than in uneaten litter. (C) 2001 Elsevier Science Ltd. All rights reserved.
Keywords: leaf litter chemistry; near infrared reflectance spectroscopy; soil macrofauna